Rendering Cliché? Visual Consumption of Video Games as Virtual-Space Leisure Activities - Kremer, Dominik; Pappenberger-Muench, Naomi; Fuchs, Martin; Jelinski, Sarah; Feulner, Barbara; Walker, Blake (Gaming and Geography. A Multi-perspective Approach to Understanding the Impacts on Geography (Education), 2024)
As leisure activities, tourism and video games share the context of exploration and joy and serve the escapist fantasy. Drawing on theory of the respective field, we are able to identify even deeper similarities on how geographical space is produced by environmental storytelling and visual consumption in both cases. Both form hypergeographies highlighting only relevant fragments of space meant to provide convenience for the visitor during a stay. Can this congruence been shown by empirical analysis of gameplay and marketing materials? And how can these findings inform geo-education? In a mixed-method approach, we use digital walk-alongs to observe how players react on the identified categories during gameplay in selected games representing geographic space. In a second step, we show that marketing materials advertising tourist destinations and video games respectively also make congruent and intense use of the concepts identified. This comes at the risk that hegemonic structures known from tourism also apply to video games and can be made visible by counter-narratives from the Global South. Based on these findings, we propose to use the method asking pictures to teach students about the structural similarity and to reflect on the possible consequences.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Socio-cultural framing; Tourism; Video games; Visual consumption

Tracing Individual Experiences of Everyday Greenness: Initial Results from the SpaceLog Mobile App - Kremer, Dominik; Neuner, Andreas; Jelinski, Sarah; Stadlmeier, Anna; Schlieder, Christoph; Walker, Blake (GI_Forum, 2023)
In this paper, we introduce a conceptual shift in how to investigate visual greenness as an important factor for individual wellbeing and self-reported health in everyday mobilities. Making use of controlled vocabularies of emotions, we discuss earlier approaches to data collection in everyday environments. We developed a new mobile diary app to collect multi-modal data that would allow not only for statistical spatial analysis, but also for a deeper analysis of individual sense-making of experiences in specific locations. From a limited first test sample, we evaluated the added value of the data collection process by conducting explorative data analyses of the visual greenness in user-generated imagery. We found that, in general, our method is able to relate different types of greenness observed on site to different emotional tags.
Created from Fastlane, Scopus look-up
Keywords: greenspace; health geography; image analysis; self-reported health; VGI